Interpretation of Alterations in the Horse Erythrogram - Satué, K.; Muñoz, A.; Gardón, J.C. (Journal of Hematology Research, 2014)
The interpretation of erythrogram is pivotal to assist clinicians in diagnosis, prognosis, patient management and control of equine diseases. Relative erythrocytosis associated to dehydration and blood splenic mobilization are common in horses. Absolute erythrocytosis appears less often in the horse and it can be related to increased erythropoietin concentrations, as happen in chronic hypoxic situations, neoplasias and paraneoplasic syndromes. Even less common, primary absolute erythrocytosis or polycythemia vera has been also described in horses. Anemia is a very common equine hematological disorder. The classification between regenerative and non-regenerative is difficult in this species, because peripheral signs of regeneration are not common in horses, despite having an intense regenerative anemia. This classification would need in many cases a bone marrow biopsy. The most common causes of anemia in horses are acute and chronic blood loss, hemolytic anemia and anemia of chronic disease. Assessment of peripheral blood smears is also an important tool for diagnose a hematological disorder in a horse. It should be taken into consideration that rouleaux formation and echinocytes (spiculated regular erythrocytes) are physiological characteristics of equine blood, in opposite to what happen in other animal species. Abnormal erythrocyte shapes described in horses are spherocytes, target cells, leptocytes, acanthocytes, schistocytes and leptocytes. The most common erythrocyte inclusions are, Howell-Jolly bodies (nuclear remnants, sometimes associated to rapid bone marrow maturation), Heinz bodies (indicative of oxidative damage) and hemoprotozoan parasites, such as Babesia caballi and Theileria equi.